Alligator (Alligator mississippiensis) Aquaculture in the United States. Issue 1 (2nd January 2018) - J. Nickum, Mary; Masser, Michael; Reigh, Robert; Nickum, John G.
ABSTRACT: Commercial production of American alligator ( Alligator mississippiensis ) under intensive aquaculture conditions began in the 1980s. During the last 30 years, alligator farming has become an aquacultural industry worth millions of dollars in the southern United States. In 2014, farmers in Louisiana, the nation's largest producer of captive-reared alligators, sold more than 383, 000 skins valued at more than 77 million. Most alligator farming operations utilize wild-sourced eggs, which are collected from wetland habitats under the authority of permits issued by State agencies. Typically, these permits include a requirement to return a portion of farm-reared animals to the same area where eggs were collected to maintain wild populations. Intensive rearing of alligators requires an abundance of warm water and good quality food. Extruded feeds formulated specifically for alligator are the industry standard in modern production systems. Disease can be an occasional problem in alligator production operations but risks can be minimized with provision of clean water, high-quality feed, and good hygienic conditions in grow-out facilities. Belly skins are the primary product of alligator aquaculture, but alligator meat is also sold in niche markets. Although products made from alligator skins have strong consumer appeal, the relatively high cost of products made with alligator leather limits sales to more affluent consumers. Growth of alligator farming, using current production methods, will be limited by the natural productivity of the wild resource upon which the industry depends and demand for products utilizing alligator leather. From 2004 to 2013, global demand for skins of all species of crocodilians averaged 1.4 million skins annually, of which 24.3% were American alligator.